Implementasi Metode OCRA Dan ROC Rekomendasi E-Commerce Terbaik Dalam Peningkatan UMKM - Al-Adawiyah, Robiah; Halawa, Advent (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This research aims to implement the OCRA (Ordering and Ranking with Criteria) and ROC (Rank Order Centroid) methods in providing the best e-commerce recommendations to improve the performance of MSMEs (Micro, Small and Medium Enterprises). The OCRA method is used to assess various relevant criteria, such as cost, ease of use, and market reach, while ROC is used to determine the final ranking of each e-commerce platform. The research results show that Bukalapak received the highest final preference score of 0.2324, making it the main choice for MSMEs. It is hoped that these findings can help MSMEs choose the most suitable e-commerce platform, so that they can increase their competitiveness and business growth. This research makes a significant contribution to the development of digitalization strategies for MSMEs in Indonesia